"O mundo está cheio de Deus!": a mística na teologia de Martinho Lutero - Boning, Claudio (2013)
The subject of this paper is the mysticism which underlies Martin Luther s theology. Passing through the influence of medieval mysticism in Luther s theology and through the confrontation with the enthusiast movement, we point out the mystical nuances of Luther s theology. Through bibliographic research, the current tendencies with regard to this theme are presented. We highlight the research carried out by the Finnish researchers, initiated by Tuomo Mannermaa who has pointed out the importance of the concept of unio mystica in Luther s theology. Likewise, we will present the diversification of this research and its reception by the German and North American theologians. Luther s contribution to Latin American reflection will be brought to light, highlighting the convergences of Luther s mysticism with the Liberation mysticism. The first chapter will deal with Luther s context. The second chapter will deal with the criticism which Luther made of the speculative mysticism which influenced the enthusiast movement and the mysticism present in Luther s theology. The third chapter presents the current panorama of the research on mysticism in Luther. The Finnish contribution is the most significant in this area. In the Finnish research the presence of Christ in the faith is central. Without this real presence it would be impossible to speak of unio. Besides this, we will present the diversification of the Finnish school and receptions in the areas of German and North American theology. The final movement of our paper will be to reflect on the contributions of Luther s mysticism for the current reflection on Christian mysticism for our context.